1986
DOI: 10.1128/jcm.23.3.431-433.1986
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of exogenous siderophores by Campylobacter species

Abstract: The availability of iron to potentially pathogenic bacterial strains is restricted by the iron-binding proteins of the host. In this study, we examined 40 strains of Campylobacter species grown under iron-limiting conditions. While the strains produced no detectable siderophores, all the isolates freely utilized exogenous siderophores produced by other organisms as iron carriers. These data suggest that the use of an exogenous siderophore (either purified or present in a coinfecting microorganism) may be impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…It is also possible that the fag genes are responsible for the uptake of a siderophore which is not produced by C. pseudotuberculosis, but which C. pseudotuberculosis can scavenge in vivo, from other bacteria. This latter scenario is observed with organisms such as Campylobacter species [20] and may be supported by the lack of siderophore biosynthetic genes clustered with the fag genes.…”
Section: Utilization Of Iron Sources By a C Pseudotuberculosis Fagb(mentioning
confidence: 77%
“…It is also possible that the fag genes are responsible for the uptake of a siderophore which is not produced by C. pseudotuberculosis, but which C. pseudotuberculosis can scavenge in vivo, from other bacteria. This latter scenario is observed with organisms such as Campylobacter species [20] and may be supported by the lack of siderophore biosynthetic genes clustered with the fag genes.…”
Section: Utilization Of Iron Sources By a C Pseudotuberculosis Fagb(mentioning
confidence: 77%
“…They, however, cannot synthesise ferrioxamines themselves, but may be available from related species and other members of normal gut microbiota (Champomier-Verges et al, 1996;Kingsley et al, 1999). Examples of other genera that can utilise heterologous siderophores are Campylobacter and Pseudomonas (Baig et al, 1986;Champomier-Verges et al, 1996;Llamas et al, 2006). A study with microbial isolates from marine sediments indicated that the growth of many bacteria depends on siderophore production by other bacteria within the same community (D'Onofrio et al, 2010).…”
Section: Iron Cross-feeding With Heterologous Siderophoresmentioning
confidence: 99%
“…Neisseria gonorrhoeae for example uses aerobactin [172], as does the Gram positive organism Corynebacterium diphtheriae [173]. Haemophilus influenzae, H. parainfluenzae and H. paraphrophilus [174], Pseudomonas aeruginosa [175] and Campylobacter jejuni [176,177] can all utilise enterochelin.…”
Section: Siderophore Systems In Other Bacteriamentioning
confidence: 99%